Biological Control of Acaudalerodes Rachipora (Singh) (Hemiptera: Alerodidae) by the Entomopathogenic Fungi on in Field (Baghdad Science Journal, 2025)
This study was conducted in the College of Agriculture fields /University of Baghdad, during Autumn 2013. This study was aimed to examine the mortality rate on the all black fly stages of Acaudalerodes rachipora Singh) by the biotic fungus Beuveria bassiana. The results of a preliminary survey showed that the samples of Ziziphus spaina christi were infested by blakflies in Agriculture collage during Autumn seasons of 2013 , the presence of species of black flies A. rachipora on the lower surface of the leaf, the study aimed to study and research the effects of fungus B. bassiana on black fly A. rachipora. After six days of treatment results showed the continued superiority 106 spore / ml trends in the western, southern and eastern being 34.64, 31.77 and 20.8% respectively, while outweigh the moral fungus concentration 108, which was treated by insect instars in the direction north by killing 26.32% on the rest concentrations of fungus, which was treated by insect instars to the same direction the latter, note from the results above the high mortality rates with time as increased rates of initial mortality rates,. Finally reflected clearly outweigh the concentration of 108 fungus spore / ml in all directions western, southern, northern and eastern mortality rates 65.35, 62.84, 50.89 and 46.34%, respectively, compared with mortality rates made by the concentrations of other used in the experiment of the directions of the four that did not show significant differences in their impact on the roles of insect and thus increased mortality rates in the field with the time. We recommend conducting further field studies of fungus to determine the extent of efficiency in the field, according to local conditions and to determine its role in regulating the population of black flies and study the compatibility of the fungus with other control methods.